(untitled) (Medico Legal Update, 2021)
Physics plays a vital role in cultivating the knowledge of natural sciences and establishing the foundation of logistic and scientific method. The application of physics to medical sciences has been developed in practice for centuries. X-Ray, CT scan and MRI images of the spine provide a practical approach for detecting and assessing vertebral abnormalities. For accurate vertebra detection number of features of an image can be extracted and meaningful information can be obtain from low level information in the image using segmentation. In this paper a method is proposed for making treatment of spinal traction efficient and feasible by using image processing algorithm based on the data obtained from the survey and images of the patients.